If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 2x = 6 + 4x Solving 18 + 2x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 18 + 2x + -4x = 6 + 4x + -4x Combine like terms: 2x + -4x = -2x 18 + -2x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 18 + -2x = 6 + 0 18 + -2x = 6 Add '-18' to each side of the equation. 18 + -18 + -2x = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 6 + -18 -2x = 6 + -18 Combine like terms: 6 + -18 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| (5x-4)=(4x-7)+1 | | Y*t=6y*t-1 | | X+x+3=x+6 | | (-4)*(-5)-(2)*(5)= | | 3(x+5)+7x=-2x-3 | | -21*(-25)= | | 6(8+9)= | | -16+12+-11+-28= | | Z^2=6+4i | | (1-y*x^2)dx+x^2*(y-x)dy=0 | | Yt=6yt-1 | | -10*-6= | | -64*-4= | | 15+6=-14n-1 | | 9+6(2c-6)= | | 3x+26=51+2x | | (1/x)+(1/3x)+(1/x-1)=2/3 | | 5(y-3)=2(y-15) | | x(x+2)=45 | | 7*(-6x-3)=-3*(-3x+3)-1 | | 5x+9=-86 | | 1/x+1/3x+1/x-1=2/3 | | 10-3(2x+4)=-11 | | 3(n-5)n-5=21 | | -21.7-1.5= | | 4(4)+3y=16 | | 4x+3(5x-20)=16 | | 2x+5yz=100 | | 5(x-10)=8(x-7) | | f(x)=x^2+2kx+k | | -2(5+x)=3 | | -2(5+x)=-3 |